Personalising english acquisition through mobile learning - Mosquera Gende, Ingrid; Conde del Río, Alba (EDULEARN16: 8TH International conference on education and new learning technologies, 2020)
Free mobile applications can be a substantial complement to achieve a personalised learning experience for our students, not only in the acquisition of English language but also in other subjects or competences. However, focusing on English, the great amount of applications available provides the perfect environment to adapt teaching to the actual level of our students. One of the problems when teaching and learning a language is that classes are normally very heterogeneous in their level, making it difficult to reach learners with a higher level and those with a lower level at the same time. Mobile learning can help teachers with that issue, including two important aspects. On the one hand, we would motivate students through the usage of their most beloved gadget and, on the other hand, we would facilitate different applications to each of them, depending on their individual needs and English knowledge. The methodological and teaching basis of this approach has to do with the relevance of improvement over achievement. That is, perhaps not all the students can reach the same point in the same period of time, because neither their point of departure nor their experience with the English language is the same. Admitting that premise, personalised learning is possible and efficient. Apart from that, using mobile applications also facilitates different learning styles and improves the assistance with learning difficulties.
Keywords: m-learning; english; mobile applications; language; education; personalised education; personalized education; learning styles; learning difficulties; WOS(2)